(untitled) (Journal of African Studies and Ethnographic Research, 2021)
Myths and legends have been extensively studied in orature even though they have been given a facile analysis. This qualitative desk top research presents an in-depth examination of Lwanda Magere folklore by bringing to perspective its images, signs and symbols and exposing their literary functions while theorizing the human body as a text. The study used the human body as text theory to analyse data. Berger (1987) notes that, ‘Looking fixedly at certain phrases sitting on the page, they begin to move, change shape, dance, wriggle, turn inside out, sprout wings and fly about flapping from one speech or speaker to another until my wits begin to turn.’ Berger’s finding in literary words applies intrinsically to human bodies and objects as texts. The paper has examined human bodies in gender, military and economic senses and data from the Lwanda Magere narrative as well as narratives from foreign folklore have been subjected to textual analysis and their discussions extended to touch on human bodies as prostheses, cyborgs and weapons in futuristic science fiction. The study found out that life dramatically changes when we continue to integrate scientific and technological elements into the human body. The result will affect ethics, morality, justice, economics and to a large extent what it means to be human in the future.